2007
DOI: 10.1111/j.1540-8175.2007.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Late Supraclavicular Echo Doppler Reliably Predict Angiographical String Sign of Lima to Lad Area Grafts?

Abstract: Postoperative supraclavicular duplex as a method to assess the patency of LIMA to LAD area grafts allows discriminating functional grafts from (distal) string sign grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Despite accurate and reliable assessment of native LITA before CABG, we cannot succeed to identify in situ LITA graft accurately after CABG at initial. This is partly because of unfavorable chest wall configuration, coexistent lung diseases and the learning curve experience (25 et al (26) stated that obtaining LITA graft non invasively with the transthoracic approach is difficult because of its narrow lumen and constant pulsatile movement. Therefore they evaluated the LITA graft flow with echo Doppler from the supraclavicular approach because the proximal part of the LITA graft is close to the chest wall and fixed with soft tissue and hence free from pulsatile displacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite accurate and reliable assessment of native LITA before CABG, we cannot succeed to identify in situ LITA graft accurately after CABG at initial. This is partly because of unfavorable chest wall configuration, coexistent lung diseases and the learning curve experience (25 et al (26) stated that obtaining LITA graft non invasively with the transthoracic approach is difficult because of its narrow lumen and constant pulsatile movement. Therefore they evaluated the LITA graft flow with echo Doppler from the supraclavicular approach because the proximal part of the LITA graft is close to the chest wall and fixed with soft tissue and hence free from pulsatile displacement.…”
Section: Discussionmentioning
confidence: 99%
“…It shows high specificity, prevents invasive investigations and improves in patients with postoperative angina. Hartman et al (26) reported that peak diastolic and systolic velocities are the most discriminative factors for string sign LITA grafts and suggest postoperative supraclavicular duplex as a method to assess the patency of LITA to LAD area grafts allows discriminating functional grafts from string sign grafts. We want to mention one of our cases for supporting this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…A noninvasive method for risk stratification and clinical follow-up would be useful in those patients. The value of color Doppler ultrasonography (CDUS) with the supraclavicular approach for preoperative evaluation of the native LIMA as well as for the postoperative detection of LIMA graft patency was recently suggested [10, 11]. These studies focused mainly on the parameters of the ratio of peak flow velocities during the diastolic and systolic period or each parameter (the peak systolic velocity [PSV], peak diastolic velocity [PDV], and end-diastolic velocity [EDV]) on CDUS individually.…”
Section: Introductionmentioning
confidence: 99%